Peran Orang Tua Tunggal (Single Parent) Dalam Menanamkan Karakter Religius Pada Remaja - Najjatul Mudzakiroh; Muhamad Arif (Program Studi Pendidikan Agama Islam, 2022)
The phenomenon of the life of children without fathers can be found in Miru village, Kedamean sub-district, Gresik regency. Incomplete families are caused by various conditions, such as the head of the family who has passed away earlier, died while on duty, divorce or what is becoming a current trend due to the post-covid-19 pandemic. The focus of this research is: What is the role of a single parent in instilling religious character in adolescents in the Miru Kedamean Gresik hamlet? What are the supporting and inhibiting factors for the role of a single parent in instilling religious character in adolescents in Miru Kedamean Gresik hamlet? This research is included in qualitative research. Methods of data collection using interviews, observation, and documentation. The primary data sources in this study were hamlet heads and single parents in Miru Banyuurip Kedamen Gresik hamlet, while data analysis techniques used Miles and Hubarman's theory. The results of the study show that 1) The role of a single parent or single parent is very important to the religious character of adolescents which includes the following: a) The obedience to worship of a child from a single parent is influenced by how often the parents themselves give orders. b) The time discipline of a child from a single parent is influenced by the firmness and emphasis of parents on children. c) The morals and decency of children are influenced by the behavior of parents towards their children. d) The exemplary behavior of single parents, such as always using the word